Robust Audio Watermarking Algorithm Based on Empirical Mode Decomposition. Issue 6 (1st November 2016) - Tang, Xin; Ma, Zhaofeng; Niu, Xinxin; Yang, Yixian
Abstract : A novel robust audio watermarking algorithm based on empirical mode decomposition is proposed. The intrinsic feature of the final residual decomposed from the audio frame is selected to embed watermark and the algorithm works by shifting each element of the final residual to make its sum greater or less than 0. The experimental results show that the proposed algorithm does not change the property of the final residual after embedding watermark and the watermark is robust against various kinds of attacks. Compared with existing classic algorithms based on Empirical mode decomposition (EMD), the proposed algorithm largely improves both the robustness and imperceptibility of watermarking.